Genome-wide analysis of soybean DnaJA-family genes and functional characterization of GmDnaJA6 responses to saline and alkaline stress - Binshuo Zhang; Zhen Liu; Runnan Zhou; Peng Cheng; Haibo Li; Zhiyang Wang; Ying Liu; Mingyang Li; Zhenqing Zhao; Zhenbang Hu; Qingshan Chen; Xiaoxia Wu; et al. (Crop Journal, 2023)
Plant DnaJA proteins act as molecular chaperones in response to environmental stressors. The purpose of this study was to characterize the function and regulatory mechanisms of DnaJA genes in soybean. Gene expression profiles in various soybean tissues at various stages of development indicated that GmDnaJAs function in the coordination of stress and plant hormone responses. GmDnaJA6 was identified as a candidate regulator of saline and alkaline stress resistance and GmDnaJA6 overexpression lines showed increased soybean saline and alkaline tolerance. DnaJ interacted with Hsp70, and GmHsp70 increased the saline and alkaline tolerance of plants with chimeric soybean hairy roots.